Examination of University Students⿿ Foreign Language Classroom Anxiety - Ergin, Atilla; Bademcioglu, Mehtap; Karataş, Hakan; Alci, Bülent (Elsevier BV, 2016)
AbstractAnxiety has been found to interfere with many types of learning. And, many researches such as MacIntyre and Gardner (1989) indicate there is a negative relationship between anxiety and second language learning achievement. In current study, it was aimed to determine whether the students⿿ foreign language classroom anxiety (FLCA) display significant differences on the basis of gender, language level, receiving English preparatory training, and the kinds of high school they graduated from. The research group included 320 male (65.6%) and 168 female (34.4%) English preparatory students at Istanbul Technical University. Foreign Language Classroom Anxiety Scale developed by Horwitz, Horwitz and Cope (1986) and adapted in Turkish by Aydın (2001) was used as the data collection tool. Data were analysed using independent samples t-test, one-way ANOVA and the Scheffe's post-hoc test. T-test results showed female students⿿ FLCA score is higher. But, there was not a statistically significant relationship between FLCA and receiving preparatory training. ANOVA results indicated high school differentiation does not affect it. Yet, Scheffe's test findings demonstrated the students⿿ FLCA change over depending on their language level. In other words, female students are more appropriate to suffer from FLCA and FLCA is affected by students⿿ language level.
Keywords: Foreign Language Classroom Anxiety; Anxiety